A new species of Furculanurida (Collembola: Neanuridae) from Ivory Coast, with comments on related genera - Zon, Serge Demeango; Tano, Yao; Deharveng, Louis (Zootaxa, 2014)
A new species of Pseudachorutinae, Furculanurida emucronata sp. nov., is described from Lamto in the Ivory Coast. It differs from all known Pseudachorutinae species by the presence of a strong lateral tooth on the claw of leg I, and from other species of the genus Furculanurida by the absence of a mucro. It is provisionally assigned to the genus Furculanurida which is redefined accordingly. The heterogeneity of the genus is stressed, and its relationships with Arlesiella, Kenyura, Pseudachorutes and Stachorutes are discussed.